2014
DOI: 10.1186/1748-5908-9-21
|View full text |Cite
|
Sign up to set email alerts
|

Comparing in-person and webinar delivery of an immunization quality improvement program: a process evaluation of the adolescent AFIX trial

Abstract: BackgroundImmunization quality improvement programs are often limited by the cost and inconvenience associated with delivering face-to-face consultations to primary care providers. To investigate a more efficient mode of intervention delivery, we conducted a process evaluation that compared in-person consultations to those delivered via interactive webinar.MethodsThe Centers for Disease Control and Prevention’s Assessment, Feedback, Incentives, and eXchange (AFIX) Program is an immunization quality improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…One randomized study of a single session intervention delivered in-person or via webinar using Adobe Connect (Adobe Systems Incorporated) demonstrated that there was no difference in effectiveness between delivery via Adobe Connect and the in-person delivery, and they both appeared to be satisfactory to clinicians. 40 Two factors related to prescribing to disadvantaged smokers with mental illness (e.g., those with low education, income or employment) could have influenced our findings. First, this study addressed smokers with mental illness disabilities whose income is typically quite low, such that these smokers typically do not feel they can afford to buy NRT over the counter in pharmacies.…”
Section: Discussionmentioning
confidence: 86%
“…One randomized study of a single session intervention delivered in-person or via webinar using Adobe Connect (Adobe Systems Incorporated) demonstrated that there was no difference in effectiveness between delivery via Adobe Connect and the in-person delivery, and they both appeared to be satisfactory to clinicians. 40 Two factors related to prescribing to disadvantaged smokers with mental illness (e.g., those with low education, income or employment) could have influenced our findings. First, this study addressed smokers with mental illness disabilities whose income is typically quite low, such that these smokers typically do not feel they can afford to buy NRT over the counter in pharmacies.…”
Section: Discussionmentioning
confidence: 86%
“…This finding suggests that an interactive webinar is a viable way to deliver AFIX without incurring travel costs. In a separate process evaluation, 8 we calculated the cost of delivering our intervention as $152 per clinic for in-person consultations versus $100 per clinic for webinar consultations. Future studies should seek to replicate our findings in the context of early childhood AFIX because webinar delivery could significantly improve the efficiency of this nationally implemented program.…”
Section: Discussionmentioning
confidence: 99%
“…Our intervention has been described in detail elsewhere, 8 but briefly, each clinic received 1 in-person AFIX consultation (delivered April-May 2011), 1 AFIX consultation by webinar (delivered May-August 2011), or no consultation. During the consultation, which consisted of a single 60-to 90-minute session, an immunization specialist (A.M.D.)…”
Section: Methodsmentioning
confidence: 99%
“…A process evaluation comparing the in-person and virtual AFIX strategies demonstrated that the latter was significantly less expensive ($100 vs $152 per clinic). 89 …”
Section: P=002)mentioning
confidence: 99%